Development of a Highly Stable, Nonaqueous Glucagon Formulation for Delivery via Infusion Pump Systems. (1st January 2015) - Newswanger, Brett; Ammons, Steve; Phadnis, Neelima; Ward, W. Kenneth; Castle, Jessica; Campbell, Robert W.; Prestrelski, Steven J.
Background: Despite a vigorous research effort, to date, the development of systems that achieve glucagon stability in aqueous formulations (without reconstitution) has failed to produce any clinical candidates. We have developed a novel, nonaqueous glucagon formulation based on a biocompatible pharmaceutical solvent, dimethyl sulfoxide, which demonstrates excellent physical and chemical stability at relatively high concentrations and at high temperatures. Methods: This article reports the development of a novel, biocompatible, nonaqueous native human glucagon formulation for potential use in subcutaneous infusion pump systems. Results: Data are presented that demonstrate physical and chemical stability under presumed storage conditions (>2 years at room temperature) as well as "in use" stability and compatibility in an Insulet's OmniPod ® infusion pump. Also presented are results of a skin irritation study in a rabbit model and pharmacokinetics/pharmacodynamics data following pump administration of glucagon in a diabetic swine model. Conclusions: This nonaqueous glucagon formulation is suitable for further clinical development in pump systems.